2013
DOI: 10.1002/pola.26556
|View full text |Cite
|
Sign up to set email alerts
|

1:2‐sequence‐regulated radical copolymerization of naturally occurring terpenes with maleimide derivatives in fluorinated alcohol

Abstract: Naturally occurring bulky terpenes, such as (þ)-and (-)-limonene and (-)-b-pinene, were quantitatively copolymerized with maleimide (MI) derivatives (i.e., phenyl-, cyclohexyl-, ethyl-, and unsubstituted-MI) in PhC(CF 3 ) 2 OH solvent via selective 1:2alternating propagation governed by the penultimate effect, which resulted in 1:2-sequence regulated polymers with relatively high glass transition temperatures and optical activities. Similar petroleum-derived bulky olefins possessing cyclohexenyl, cyclohexyl,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
84
2
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(92 citation statements)
references
References 54 publications
4
84
2
2
Order By: Relevance
“…Recently, Kamigaito et al reported the 1/r 12 value of 0.33 in the fluorinated cumyl alcohol, PhC(CF 3 ) 2 OH, for the same copolymerization system of O3 (M 1 )−PhMI (M 2 ). 55 The 1/r 12 value observed in this study was higher than the reported one, being ascribed to the solvent effects. 58,62 It was reported that the fluoroalcohol diminished the homopropagation of PhMI via a hydrogen bonding interaction with the carbonyl Table 1).…”
Section: ■ Results and Discussioncontrasting
confidence: 78%
“…Recently, Kamigaito et al reported the 1/r 12 value of 0.33 in the fluorinated cumyl alcohol, PhC(CF 3 ) 2 OH, for the same copolymerization system of O3 (M 1 )−PhMI (M 2 ). 55 The 1/r 12 value observed in this study was higher than the reported one, being ascribed to the solvent effects. 58,62 It was reported that the fluoroalcohol diminished the homopropagation of PhMI via a hydrogen bonding interaction with the carbonyl Table 1).…”
Section: ■ Results and Discussioncontrasting
confidence: 78%
“…4 On the other hand, terpenes or terpenoids refer to one of the largest families of naturally occurring compounds and are secondary metabolites synthesized mainly by plants, particularly conifers. 8 To make use of the chemical functionalities (unsaturation, functional groups) present in terpene molecules, various chemical strategies and a wide range of polymerisation techniques [9][10][11][12][13][14][15][16][17][18][19] had been studied. Thus, due to their abundance in nature, there has been great interest in producing polymers with terpenes as either functional entities or as the main constituent.…”
Section: Introductionmentioning
confidence: 99%
“…[17,18] The sophisticated AAB-type sequence structures were produced during the copolymerization under penultimate unit control (Scheme 1). [19][20][21][22] It was previously reported that the maleimide copolymers including an allyl group in the side chain were fabricated by the combination of olefin moieties with different reactivity. [23] This was unique method for the design of a new thermosetting system including radical reaction processes for polymerization and postpolymerization reactions.…”
Section: Introductionmentioning
confidence: 99%